Following in their Footsteps: Comparing Interest Parity Conditions in Central European Economies to the Euro Countries - Kashif Mansori (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper investigates capital market integration in the major Central European emerging economies by testing the covered and uncovered interest parity conditions vis-à-vis the U.S. dollar and the DM/euro. The results for the Central European economies since 1997 are contrasted against those of the euro countries during the period preceding the introduction of the euro. This allows a comparison of conditions in the capital markets in the Central European economies versus those in the pre-euro EU. The results suggest that capital mobility and exchange rate market efficiency in Central Europe are remarkably similar to conditions in the EU during the 1990s.
Keywords: 330; covered interest parity; uncovered interest parity; Central Europe; EU enlargement